MYTHICAL CAR: METONYMY IN TAYLOR SWIFT'S SONG LYRICS - Jonathan Irene Sartika Dewi Max (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2022)
Varieties of car-related words reflect how the knowledge involving the vehicle has been stored in cultural society. The repetitive occurrence of phrases about a car in Taylor Swift’s 40 song lyrics raises a question on how such a thing is used in song lyrics to convey meaning.  This article uses Littlemore's (2015) theory to figure out the domain where metonymy is used. To explain the meaning-making process, it adopts Moore’s (2016) notion that to reach metonymy is by analyzing the semiotic property of experiential correlation and descriptions of the semiotic structure which Brandt et. al (2019). Then, a qualitative method suggested by Gravells (2018) is applied to read the interaction among language features in context. The metonymy analysis shows the songs employ the domain of car parts, car types, road areas, driving manners, and street signs as part of car metonymy. The semiotic analysis shows that the car has the mythic meaning of overcoming trouble, private space, taking action, romance, and status so that the meaning is readily grasped by the audiences. Thus, this article enriches the method of researching popular songs where language plays vital parts in the lyrics.